2015
DOI: 10.1088/0004-6256/150/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Wiyn Open Cluster Study. Lxvi. Spectroscopic Binary Orbits in the Young Open Cluster M35 (Ngc 2168)

Abstract: The young (150 Myr) open cluster M35 (NGC 2168) has been one of the core clusters of the WIYN Open Cluster Study since 1997. Over these 17 years we have obtained approximately 8000 radial-velocity (RV) measurements of stars in the M35 field, which we provide here. Our target sample consists of 1355 photometrically selected stars in the field of M35 within the main sequence and binary sequence of the cluster and within V 13 16.5 ⩽ ⩽ and B V ( ) 0.6 − ⩾ . Using our RV measurements we cleanly separate likely clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 41 publications
(76 reference statements)
2
55
2
Order By: Relevance
“…For the following populations under consideration, the level of contamination by WD companions is smaller than the measurement uncertainties, and so we assume that all observed solar-type primaries are the true primaries of their respective systems. Leiner et al (2015) obtained multiepoch high-resolution spectra of 418 confirmed and likely solar-type MS members of the M35 open cluster (τ≈150 Myr). Within this sample, they identified nine SB2s with P<100days and q>0.6 and 35 SB1s with P<1000days.…”
Section: Binary-star Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…For the following populations under consideration, the level of contamination by WD companions is smaller than the measurement uncertainties, and so we assume that all observed solar-type primaries are the true primaries of their respective systems. Leiner et al (2015) obtained multiepoch high-resolution spectra of 418 confirmed and likely solar-type MS members of the M35 open cluster (τ≈150 Myr). Within this sample, they identified nine SB2s with P<100days and q>0.6 and 35 SB1s with P<1000days.…”
Section: Binary-star Formationmentioning
confidence: 99%
“…Within this sample, they identified nine SB2s with P<100days and q>0.6 and 35 SB1s with P<1000days. The Leiner et al (2015) binary survey is sensitive to velocity semi-amplitudes K 1 ≈3 km s −1 , and so binaries with q>0.1 and P<200days are 95% complete in their sample assuming random orientations. Based on the four SB2s and 10 SB1s with P=2-20days (Δ logP=1.0), we calculate a companion frequency of 2; 0.1 = 73% ±16% of O-type stars have n2 companions with q>0.1 (magenta).…”
Section: Binary-star Formationmentioning
confidence: 99%
“…All the data except that for M35 are taken from Meibom & Mathieu (2005). For M35, the circularization period of 9.9 days is from Leiner et al (2015) and the age of 0.18 Gyr from Kalirai et al (2003). For PMS binaries, our calculation does not actually apply, because those stars have a more extended convective envelope than the Sun.…”
Section: Circularization Of Late-type Binariesmentioning
confidence: 99%
“…The timescales are calculated from equations (40) and (41) using a 1 M MESA model, and the results are divided by two assuming the binary is made of two identical stars. The black crosses with error bars represent data from Meibom & Mathieu (2005), whereas the magenta filled circle is from Leiner et al (2015).…”
Section: -6mentioning
confidence: 99%
“…However, both the binary fraction and separation distribution (and possibly the mass ratio distribution) are likely to be mass-dependent (Duchêne et al 2013) and may also be different in clusters as a result of mass segregation or dynamical evolution (e.g. Geller et al 2015;Leiner et al 2015). In principle the binary properties should be treated as a free parameter in the model RV distribution and constrained by the data, since the RV offsets caused by binarity add to the observed RV dispersion of the cluster, and the shape of the RV offset distribution due to binarity is different to the distribution of RV uncertainties (Cottaar et al 2012).…”
Section: Binaritymentioning
confidence: 99%